Analisis kreativiti guru pelatih terhadap perancangan aktiviti pengajaran dan pembelajaran bahasa arab mendepani era 4.0 - Noor Shamshinar Zakaria; Nor Azhan Norul’azmi (Penerbit Universiti Kebangsaan Malaysia, 2023)
The practice of preparing Daily Lesson Plan (DLP) among teachers is not an uncanny task. However, it still becomes an issue when the teaching and learning (T&L) turns to teacher-centered, whiteboard-oriented, relying on content and activities which merely provided by the Ministry of Education Malaysia and adopting textbooks without the support from other sources. Failure to plan activities in the DLP creatively and interestingly will result in unattainable learning outcomes. Thus, the complexity of ideas, strategic implementation and problem-solving actions in T&L become the main sticks in determining teacher’s competency. This study analyses trainee teachers’ creativity in planning Arabic T&L activities and identifies whether the elements of creativity planned are in line with the 21st century in coping with communication and technological development in 4.0 era. It uses a qualitative method through the analysis of 17 DLP writings to obtain research data. The data were analyzed based on four components of T&L activities, namely set induction, strategies, teaching aids and Higher Order Thinking Skills. Findings showed that trainee teachers practise less creativity in planning Arabic T&L activities, and it is still based on traditional methods. Elements of creativity in set induction, T&L strategies, and HOTS need to be further enhanced. Nevertheless, there are some trainee teachers who employed the latest technology that depicts the element of teachers’ creativity in Arabic T&L activities. The implications of the study indicate that trainee teachers need to plan Arabic T&L activities creatively that meet the language skills and acquisition in line with 21st century T&L activities. Furthermore, trainee teachers should incorporate their creativity in planning T&L activities and keep abreast of the latest T&L knowledge and skills.